2018
DOI: 10.1002/jcp.27569
|View full text |Cite
|
Sign up to set email alerts
|

The role of iron metabolism in cancer therapy focusing on tumor‐associated macrophages

Abstract: Iron is an essential micronutrient in mammalian cells for basic processes such as DNA synthesis, cell cycle progression, and mitochondrial activity. Macrophages play a vital role in iron metabolism, which is tightly linked to their phagocytosis of senescent and death erythrocytes. It is now recognized that the polarization process of macrophages determines the expression profile of genes associated with iron metabolism. Although iron metabolism is strictly controlled by physiology, cancer has recently been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 117 publications
(183 reference statements)
0
15
0
Order By: Relevance
“…Macrophages play a major role in iron homeostasis by recycling iron from senescent and dying red blood cells (RBC) back into the circulation and different tissues in the body (Andrews, 1999;Ganz, 2012;Hubler et al, 2015). Additionally, macrophage polarization is closely associated with iron metabolism (Dong et al, 2019). Studies have shown that over 60% of iron metabolism-related genes are differentially expressed between the M1/M2 macrophage axis (Recalcati et al, 2010).…”
Section: Iron Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages play a major role in iron homeostasis by recycling iron from senescent and dying red blood cells (RBC) back into the circulation and different tissues in the body (Andrews, 1999;Ganz, 2012;Hubler et al, 2015). Additionally, macrophage polarization is closely associated with iron metabolism (Dong et al, 2019). Studies have shown that over 60% of iron metabolism-related genes are differentially expressed between the M1/M2 macrophage axis (Recalcati et al, 2010).…”
Section: Iron Metabolismmentioning
confidence: 99%
“…IONs on the other hand, have been broadly explored in preclinical and clinical studies in the past decade (Hu et al, 2018). IONs accumulation in macrophages increased intracellular iron levels, thus promoting the proinflammatory phenotype (Laskar et al, 2013;Dong et al, 2019). Ferumoxytol, an FDA-approved ION for the treatment of anemia, inhibited tumor growth and metastatic spread in a xenograft mouse model by shifting TAM polarization toward the M1-like phenotype (Zanganeh et al, 2016).…”
Section: Iron Metabolismmentioning
confidence: 99%
“…Cluster 1 patients with lower TMB had a better prognosis than those in the other two clusters. Previous studies have shown that iron plays a critical role in the reprogramming of the TME ( 18 , 25 ). The TME is abundant with a variety of leukocytes, of which macrophages dominate.…”
Section: Discussionmentioning
confidence: 99%
“…There are now three major TAM therapies: inhibiting macrophage recruitment, depleting TAM, and promoting TAM anti-tumor transformation. For example, by blocking the most common CCL-2 and CCR-2 signaling pathways, macrophages recruitment and in ltration can be decreased, and tumor development can be delayed [29] . Some mannose-modi ed nanoliposome carriers and PLGA nanoparticle carriers selectively target the highly expressed mannose receptor (CD206) in M2 macrophages, which can accurately destroy M2 macrophages while having a low unfavorable effect on the body [30][31] .…”
Section: Discussionmentioning
confidence: 99%